The Effect of Tax Sanctions and Subjective Norms on Tax Evasion: A Case of the East Balikpapan Pratama KPP Area - Iskandar Iskandar; Edelwais Edelwais (Bulletin of Social Studies and Community Development, 2026)
This study aims to investigate the effects of tax sanctions and subjective norms on tax evasion behavior. The study employed a quantitative research approach, using questionnaire-based data collection from respondents selected through random sampling. The questionnaire items measuring tax sanctions, subjective norms, and tax evasion behavior were adapted from previous studies on taxpayer compliance and behavioral intention. The instrument used a five-point Likert scale ranging from strongly disagree to strongly agree. The collected data were analyzed using SmartPLS 4.0 to test the relationships among variables. The findings indicate that subjective norms have a significant negative effect on tax evasion behavior, suggesting that stronger social and moral pressures can reduce taxpayers’ tendency to evade taxes. In contrast, tax sanctions were found to have no significant effect on tax evasion behavior. The study concludes that subjective norms play a more important role than tax sanctions in influencing taxpayer behavior and reducing tax evasion practices. The questionnaire instrument consisted of several indicators for each variable, including tax sanctions, subjective norms, and tax evasion behavior. The measurement items were adapted from prior studies in taxation and behavioral research. Subjective norms were measured using indicators of social influence and perceived expectations from important others, while tax sanctions were measured through respondents’ perceptions of penalties and legal consequences for tax violations. Tax evasion behavior was measured using indicators of respondents’ attitudes and tendencies toward tax avoidance. All items were measured using a five-point Likert scale (1 = strongly disagree to 5 = strongly agree). Before the main survey was conducted, the instrument underwent validity and reliability testing. The results showed that all constructs met the validity requirements, and the reliability test indicated acceptable Cronbach’s alpha values of 0.70 or higher for all variables. Keywords: Tax Sanctions, Subjective norms, Tax Evasion, WPOP that does freelance work.